Head and Neck Lymphatics - Frank Reilly; Edwin Allen (Association of American Medical Colleges, 2010)
Abstract This resource is an interactive web-based tutorial that was developed in Viewpoint and Macromedia Flash to model the structure and function of the lymphatic system in the head and neck. The tutorial was designed to stimulate self-directed and problem-based learning by creating simulations and a quiz of the normal patterns of lymphatic drainage for dental and medical students' self-assessment and feedback. The tutorial is user friendly and achieves a dimension that cannot be attained by using conventional textbooks. Learners manipulate appropriate elements on the computer screen to access content and elicit feedback for self-assessment. The tutorial complements didactic and practical (dissection) activities of beginner health care professionals enrolled in the head and neck component part of human anatomy courses. A retrospective review of existing data that summarized the exam performance of 856 first-year medical students on 228 exam questions over a 9-year period was conducted. Since deployment of the courseware in 2001, significantly more students (8%; p < .05) have scored correct answers on written block exam questions. The experimental groups were exposed to didactic lectures, dissection labs, and web-based lecture notes and interactive learning objects, while the control groups were limited to didactic lectures and the dissection labs. Learner surveys from this study rated the virtual patient simulations the highest (p < .05) among the interactive resources provided for the preclinical human structure course.